The clinical characters and gene detection in a familial temporal lobe epilepsy with auditory aura. (April 2020) - Zhang, LiPing; Jia, Yu; Wang, YuPing
Highlights: We collected the clinical data of 7 familial temporal lobe epilepsy. LGI1 was the main virulent gene of auditory aura in familial epilepsy. The inheritance mode of familial temporal Lobe epilepsy was autosomal dominant. Abstract: Auditory aura was the very important clinical character in familial temporal Lobe epilepsy. LGI1 was the main pathogenic gene. The inheritance mode of this disease was autosomal dominant. We describes the clinical characters and gene detection in 7 patients in a temporal lobe epilepsy family with auditory aura. All patients in this family were diagnosed as temporal lobe epilepsy and had the same mutation: the splice site mutation in No. 2 base of the intron after the first exon in gene LGI1, c.215+2T>A, which induced the abnormal expression of peptide protein after the No. 71 amino acid encoded by LGI1. Some of the antiepileptic drugs, such as carbamazepine, oxcarbazepine, could be effective.